2013
DOI: 10.1159/000346787
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fatal Opioid Overdose and Major Depression among Street-Recruited Young Heroin Users

Abstract: Background/Aims: Non-fatal opioid overdose (NFOO) and major depression (MD) are highly prevalent in heroin users. Many risk factors are known for NFOO, but studies in non-clinical samples on its relationship with MD are lacking. We aimed to examine this relationship in a street-recruited sample, controlling for potential well-known confounders. Methods: A cross-sectional study in 452 heroin users street-recruited by chain referral methods in three Spanish cities. Eligibility criteria were: age ≤30 years, heroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(82 reference statements)
0
11
0
1
Order By: Relevance
“…Specifically, a study by Wichmann and colleagues found that patients who present to the emergency room with an opioid OD are more likely to die from the OD if they are older 14 . Other studies have found that patients with higher socioeconomic status (measured in education level), female gender, mood disorders and those taking sedating medications have an increased risk of opioid OD outside the hospital 15, 16 . Interestingly, Periasamy et al found that male gender was associated with significantly higher consumption of morphine after abdominal operations 17 , which contrasts our findings that men are at lower risk of postoperative OD.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a study by Wichmann and colleagues found that patients who present to the emergency room with an opioid OD are more likely to die from the OD if they are older 14 . Other studies have found that patients with higher socioeconomic status (measured in education level), female gender, mood disorders and those taking sedating medications have an increased risk of opioid OD outside the hospital 15, 16 . Interestingly, Periasamy et al found that male gender was associated with significantly higher consumption of morphine after abdominal operations 17 , which contrasts our findings that men are at lower risk of postoperative OD.…”
Section: Discussionmentioning
confidence: 99%
“…But, considering the high rate of suicidal ideation (more than one third) and persisting depressive symptoms, sufficient antidepressant treatment is yet to be provided and would probably need to go beyond the scope of psychopharmacological treatment, encompassing psychotherapy and psycho-social support measures. Imprisonment in itself represents a risk factor for depression [70]. In the general population, ADHD and substance abuse have both been identified as independent risk factors for lifetime suicidal ideation [71].…”
Section: Discussionmentioning
confidence: 99%
“…(5) We assumed that the annual FOR was constant during the study period, which is supported by the lack of statistical differences in the NOR between participants at baseline and those with updated information during follow-up. (6) Unfortunately, the inclusion of more independent variables in the models was not statistically possible due to the low number of deaths observed and consequent residual confounding due to uncontrolled factors such as depression [26] is possible; nevertheless, analyses were adjusted by the main sociodemographic factors and by the route of drug administration. (7) Some people classified at baseline as never having injected could have started injecting during follow-up without being detected [27].…”
Section: Discussionmentioning
confidence: 99%